Child migration & human rights in a global age - Bhabha, Jacqueline (Human rights and crimes against humanity, 2014)
"Why, despite massive public concern, is child trafficking on the rise? Why are unaccompanied migrant children living on the streets and routinely threatened with deportation to their countries of origin? Why do so many young refugees of war-ravaged and failed states end up warehoused in camps, victimized by the sex trade, or enlisted as child soldiers? This book provides the first comprehensive account of the widespread but neglected global phenomenon of child migration, exploring the complex challenges facing children and adolescents who move to join their families, those who are moved to be exploited, and those who move simply to survive. Spanning several continents and drawing on the actual stories of young migrants, the book shows how difficult it is for children to reunite with parents who left them behind to seek work abroad. It looks at the often-insurmountable obstacles we place in the paths of adolescents fleeing war, exploitation, or destitution; the contradictory elements in our approach to international adoption; and the limited support we give to young people brutalized as child soldiers. Part history, part in-depth legal and political analysis, this powerful book challenges the prevailing wisdom that widespread protection failures are caused by our lack of awareness of the problems these children face, arguing instead that our societies have a deep-seated ambivalence to migrant children--one we need to address head-on. Child Migration and Human Rights in a Global Age offers a road map for doing just that, and makes a compelling and courageous case for an international ethics of children's human rights"--Publisher description.